The Feasibility and Acceptability of a Community-Developed Health Insurance and Financial Toolkit for Emerging Adults With Type 1 Diabetes. Issue 3 (June 2022) - Blanchette, Julia E.; Allen, Nancy A.; Litchman, Michelle L.
Purpose: The purpose of the study was to assess the feasibility and acceptability of a financial stress and health insurance education toolkit developed by a community advisory board for emerging adults, ages 18 to 25, with type 1 diabetes. Methods: This study is a longitudinal, randomized controlled trial that enrolled 39 emerging adults with type 1 diabetes. Participants randomized to the intervention group were given access to the T1D Financial Toolkit, an online financial and health insurance education toolkit, over 30 days. For the present analysis, feasibility was assessed by enrollment and attrition. Optional, qualitative interviews were conducted upon the conclusion of the intervention to evaluate feasibility, acceptability, satisfaction, and key recommendations for improvement. Results: Of the 39 participants who enrolled, 36 completed the study. The intervention period had 100% completion in both the control and intervention groups. Eleven participants from the intervention group completed interviews. Participants described few challenges accessing the toolkit and were highly satisfied with the intervention aesthetics, display, and content. Key recommendations included integrating more applied problem-solving into the experience of watching the videos. Conclusions: The T1D Financial Toolkit is a financial and health insurance education intervention tailored to emerging adults with type 1 diabetes. This resource is feasible, acceptable, and satisfactory. Diabetes care and education specialists can utilize this tool in practice to provide relevant, developmentally tailored education to emerging adults with type 1 diabetes, prompt applied problem-solving, reduce barriers to self-management, and improve psychosocial outcomes.